The level of creativity in English writing among Jordanian secondary school students - Rababah, Luqman M.; Mohamed, Abdul Halim; Jdaitaw, Malek T.; Melhem, Nour Z. Bani (IISTE, 2013)
The aim of this study is to explore the level of creativity in English writing among Jordanian secondary school students.The researchers have used a random sample of 100 students of secondary school students in Irbid and Amman cities in Jordan.Adapetd Torrance Test of Creative Thinking (TTCT) was used to measure their creativity in English writing.TTCT test is thought to be the best test to evaluate the creativity dimensions of students in writing.TTCT assesses fluency or the number of ideas; flexibility, the variety of categories in the answers; and originality, which consists in considering innovative answers, neither familiar nor inappropriate.The results of the study showed that the respondents fall in the moderate level of creativity.